Do contravention attempts affect public support for presidential term limits?: Evidence from sub-Saharan Africa. Issue 1 (2nd January 2022) - McKie, Kristin; Carlson, Elizabeth
ABSTRACT: Leaders in many African countries have attempted to subvert constitutional limits on the number of terms they can serve in office. By comparing attitudes among citizens who have experienced term limits challenges and those who have not (yet), we show that these attempts have driven a backlash: on average, citizens who experience a contravention attempt become significantly more likely to say they support term limits, especially if the challenge is successful and term limits are lifted. We argue that term limit challenges make salient the possibility of a "president for life" and find that the backlash is greatest among those who are likely to be most alarmed by the prospect: those who oppose the current regime, those who are not thriving economically and those who most strongly support democracy over one-party rule.